A Qualitative Study of the Experience of Peer Workers in the Czech Republic - Balková, Miluše (Community mental health journal, 2022)
The study deals with the employment of people diagnosed with mental illness in the position of peer worker. The aim is to demonstrate through semi-structured interviews the involvement of peer workers in the social services for people diagnosed with mental illness and to identify the influences that affect the success of peer workers involvement in services. The results of the interviews were divided into two categories (Position Specifics, Ethical Aspects) and four subcategories (Professionalism, Risk Moments, Stigmatization, Shared Values) using the Coding Method. The individual subcategories were further subdivided in detail. The results show that the most negative influence on the successful involvement of peer workers is the unclear definition of the job role and responsibilities and further, from an ethical point of view, it is the fear of subsequent labelling (stigmatization) in the search for a new job. A positive ethical influence is the sharing of social values (hope, recovery, friendship, sharing, etc.), which supports the peer worker. The study could help anchor the role in practice and could be the basis for further research in human resources management, social work and management.
Keywords: Mental Disorders; lidé; Peer Group; Czech Republic; duševní poruchy; Qualitative Research; kvalitativní výzkum; Employment; Humans; vyrovnaná skupina; Česká republika; zaměstnanost